Faktor-Faktor yang Mempengaruhi Penerapan PHBS di Wilayah Pesisir Kecamatan Tabukan Tengah Kabupaten Kepulauan Sangihe - kasaluhe, Meityn Disye; Ferdinand gansalangi; Jelita Siska Herlina Hinonaung (Jurnal Kesehatan Qamarul Huda, 2024)
The clean and healthy living behavior program (PHBS) is a form of community empowerment that focuses on preventive and promotive efforts and has an impact on the quantity and quality of the Healthy Family Index (IKS) and Healthy Community Index (IIS). PHBS aims for every member of society to become a pioneer in implementing clean and healthy living behavior in their daily lives. This Study aimed to determine the factors that influence the implementation of PHBS in the coastal area of Tabukan Tengah District, Sangihe Islands Regency.   The type of research used was analytical survey research with a cross sectional approach. Sampling method used a convenience sampling with a total sample of 127. The results showed that the frequency distribution of PHBS implementation was in the good category 65 (52.4%), the frequency distribution of low family income was 97 (78.2%) with the p-value was 0.127. Distribution of knowledge was in the good category 72 (58.1%) with p-value 0.146. Distribution of attitudes in the good category 75 (60.5%) with p-value 0.002. Distribution of health infrastructure in the available category 103 (83.1%) with p-value 1. Distribution of health workers' attitudes in the good category was 76 (61.3%) and the p-value was 0.001. There was a relationship between the respondent attitudes and health workers attitudes with the implementation of PHBS in household settings in the Central Tabukan District, Sangihe Islands Regency.